1995
DOI: 10.1021/om00008a045
|View full text |Cite
|
Sign up to set email alerts
|

The Silylium Ion (R3Si+) Problem: Effect of Alkyl Substituents R

Abstract: The X-ray structures of four R~S~( B I -~-C B~~H~) species have been determined (R3 = Et3, i-Pr3, t-Bu3, and t-BuzMe). Br6-CBllH6-is a particularly weakly coordinating anion and leads to long Si-Br bond distances (ca. 2.43-2.48 A). The developing silylium ion character in these species is reflected in the approach of the R3Si6+ moiety toward planarity. The sum of the C-Si-C angles for each of the four derivatives lies in the range ca. 345-351". The closest approach to 360" is found in the triisopropyl derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(147 citation statements)
references
References 10 publications
5
141
0
1
Order By: Relevance
“…The average Ge-C bond length is 1.943 Å . In the corresponding Si compound, 23 the sum of the C-Si-C angles is 349.0°and the Si-Br bond lengthening is ca. 0.23 Å .…”
Section: Resultsmentioning
confidence: 99%
“…The average Ge-C bond length is 1.943 Å . In the corresponding Si compound, 23 the sum of the C-Si-C angles is 349.0°and the Si-Br bond lengthening is ca. 0.23 Å .…”
Section: Resultsmentioning
confidence: 99%
“…[30] To probe the stability of a ferrocenyl-substituted silicon cation in the presence of such stabilizing substituents the synthesis and ring-opening of fcSiiPr 2 (3 c) were undertaken.…”
Section: Simentioning
confidence: 99%
“…Surprisingly, the closest approach to planarity was found for the tri-iso-propyl derivatives, rather than for the tri-tert-butyl species. The authors also concluded that hyperconjugative stabilization of the cationic silicon centre is not negligible, although it is less pronounced than in carbocations 90 . The hexachloro carborane anion was found to be the least coordinating and, based on structural, energetic and NMR criteria, more than 50% silicenium ion character was assigned to the i-Pr 3 Si υC (Cl 6 CB 11 H 6 ) υ complex 91 21.…”
Section: Interactions With Lewis Bases: Binary and Ternary Complexesmentioning
confidence: 98%
“…Reed's group reported the X-ray structures of trialkyl-silicenium ions R 3 Si C complexed to low-nucleophilic hexahalo carborane anions 90,91 . The authors varied systematically both the alkyl substituents R (R D Me, Et, i-Pr and t-Bu) and the halogen substitution of the X 6 CB 11 H 6 (X D Cl, Br, I) counterions.…”
Section: Interactions With Lewis Bases: Binary and Ternary Complexesmentioning
confidence: 99%
See 1 more Smart Citation